Overexpression and cytoplasmic localization of caspase-6 is associated with lamin A degradation in set of ovarian cancers - Callinice D Capo-chichi; Kathy Q Cai; Xiang-Xi Xu (BMC, 2018)
Abstract Background In most women with ovarian cancer, the diagnosis occurs after dissemination of tumor cells beyond ovaries. Several molecular perturbations occur ahead of tumor initiation including loss of lamin A/C. Our hypothesis was that the loss of nuclear structural proteins A type lamins (lamin A/C) transcribed from LMNA gene and substrate for active caspase-6 maybe one of the molecular perturbations. Our objective is to investigate the association between the loss of lamin A/C and the overexpression of caspase-6 in ovarian cancer cells. Method Western blotting and immunofluorescence were used to analyze the expression of lamin A/C and active caspase-6 in normal human ovarian surface epithelial (HOSE) cells, immortalized human ovarian surface epithelial cells and a set of seven ovarian cancer cell lines (including OVCAR3, OVCAR5, and A2780). The activity of caspase-6 was measured by densitometry, fluorescence and flow cytometry. Immunohistochemistry was used to evaluate the expression of caspase-6 in set of ovarian cancer tissues previously reported to have lost lamin A/C. Results The results showed that HOSE cells expressed lamin A/C and no or low level of active caspase-6 while cancer cells highly expressed caspase-6 and no or low level of lamin A/C. The inhibition of caspase-6 activity in OVCAR3 cells increased lamin A but has no effect on lamin C; active caspase-6 was localized in the cytoplasm associated with the loss of lamin A. Conclusion Overexpression and cytoplasmic localization of caspase-6 in ovarian cancer cells may be involved in lamin A degradation and deficiency observed in some ovarian cancer cells.